The Intervention of Job Satisfaction in Influence The Empowering Leadership and Talent Management Toward Staff Performance - Ris Akril Nurimansjah; Mansyur Ramly; Syahrir Mallongi; Roslina Alam; Ris Akril Nurimansjah (Pusat Penerbitan dan Publikasi Ilmiah, Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2022)
This research investigates whether and how empowerment leadership and talent management influence the mediator variables (employees’ job satisfaction) in the organization context. It also examines how the mediators should influence employees’ job performance. 575 employees were recruited for a survey study, and Structural Equation Modeling was used to test the research hypotheses. The empirical results indicate that empowerment leadership and talent management have significant and positive effects on employees’ job satisfaction. Furthermore, employees’ job satisfaction has partial mediators between predictors variables to employees’ job performance.